PENGARUH PEMBIAYAAN EKSTERNAL DALAM KUALITAS PELAPORAN KEUANGAN - Argita Rizky Oktavia; Aditya Septiani (Diponegoro Journal of Accounting, 2022)
This study aims to examine the influence of external financing such as debt financing and equity financing on quality of financial reporting. The control variable in this study are size of firm, interest distribution, and loss of firm. This study used a population of all listed firm in Indonesia Stock Exchange in 2013-2015. The sampling method in this research is purposive sampling. A criterion for firm is manufacturing companies.Total data of this study is 299 data. Multiple regression used to be analysis technique. The empirical result of this study show that debt financing has a negative effect on the quality of financial reporting and equity financing has a negative effect on the quality of financial reporting.